Bhutan Development Update, November 2018 : Accelerating Reform Momentum - World Bank (World Bank, Washington, DC, 2018)
Economic performance remains strong. Accelerating reform momentum after the 2018 general elections will be key to consolidating and furthering Bhutan’s development. Efforts aimed at enabling a vibrant and job-creating private sector will need to be prioritized. The hydropower sector has served Bhutan well, but it has not created enough jobs for the country’s educated youth. In addition, the sector has also witnessed construction delays in the past few years, which have adversely impacted growth, revenues, and exports.